Iodixanol as a Contrast Agent in a Fibrin Hydrogel for Endodontic Applications - Hertig, Gabriel; Zehnder, Matthias; Woloszyk, Anna; Mitsiadis, Thimios A.; Ivica, Anja; Weber, Franz E. (Frontiers in Physiology, 2017)
The application of biomaterials used in regenerative endodontics should be traceable. In this study, we checked some basic effects of rendering a fibrin hydrogel radiopaque using an iodine-based contrast agent (iodixanol) approved for systemic application. Fibrin hydrogels were prepared from a fibrin sealant (Tisseel) using either an isotonic iodixanol solution (Visipaque 320, test) or Tris buffer (control) as a diluent. Gelation kinetics, radiopacity, and swelling of lyophilized hydrogels were tested using standard methods. Hydrogel structure was evaluated using scanning electron microscopy (SEM). Furthermore, iodixanol release from the test gels was assessed using spectrophotometry, and tissue compatibility was compared between test and control hydrogels using the chick chorioallantoic membrane (CAM) assay. Results were compared using pairwise t-test, p < 0.05. Iodixanol caused a 70-fold delay in gelation of 26 min in the test compared to the control hydrogels (22±1 s). Radiopacity of the test gels was 1.9±0.2 mm Al/mm, compared to zero in the control hydrogels. Lyophilized hydrogel swelling was strongly reduced when iodixanol was added to the hydrogel (p < 0.05). Test hydrogels had an altered SEM appearance compared to controls, and exhibited a reduced porosity. Iodixanol release from the test hydrogels reached 14.5±0.5% after 120 h and then ceased. This release did not have any apparent toxic effect and did not affect the viability, physiology, and vascularization of the CAM of fertilized chicken eggs. Iodixanol can render a fibrin hydrogel radiopaque and maintains its tissue compatibility, yet impacts gelation kinetics and hydrogel porosity.